Oscillococcinum for influenza treatment - Luigi Alberto Marrari; Laurence Terzan; Gilles Chaufferin (Istituto Superiore di Sanità, 2012)
The use of a complementary medicine approach, and specifically of the popular medicine Oscillococcinum, for the treatment of influenza-like syndromes remains controversial. This brief paper analyses the currently available literature on this homeopathic preparation and the Cochrane Collaboration's 2006 systematic review, along with other recent studies, in order to clarify certain fundamental aspects of its use in the treatment of influenza. In the light of the reported findings, and applying the rigorous criteria of evidence-based medicine, we suggest that this medicine should be placed in category "BI".